Muni paglalayag sa pamimilosopiyang Filipino - Cariño, Jovito V.; University of Santo Tomas Publishing House (Manila UST Publishing House, 2018)
Philosophy of being Filipino, in reference with languages, practices, and politics.
Includes bibliographical references.
In Tagalog.
Keywords: Philosophy, Philippine; Values -- Philippines